THE EFFECT OF BUSINESS CAPITAL, WORKING HOURS, AND LENGTH OF BUSINESS ON THE INCOME OF STREET VENDORS IN THE GOR H. AGUS SALIM AREA, PADANG CITY - Dharmawan, Feny; Elikal Marna, Jean (Penerbit Lafadz Jaya, 2025)
This study aims to determine the effect of business capital, working hours, and length of business on the income of street vendors in the Gor H. Agus Salim Area, Padang City. This research is descriptive associative research. The population is all street vendors in the Gor H. Agus Salim Area, Padang City as of August 2024, totaling 2,305 street vendors who are permanent traders, with a sample size of 96 street vendors. The sampling technique used purposive sampling. The collection technique used a questionnaire technique. Data analysis used multiple linear regression analysis. The results of this study indicate business capital has a significant effect on the income of street vendors, so that hypothesis 1 is accepted. Working hours has a significant effect on the income of street vendors, so that hypothesis 2 is accepted. length of business does not have a significant effect on the income of street vendors, so hypothesis 3 is rejected. Business capital, working hours and length of business simultaneously has a significant effect on the income of street vendors, so that hypothesis 4 is accepted.